+0

# If and , then what is ?

0
202
3

If  and , then what is ?

Guest Jan 29, 2015

#3
+81023
+5

Using x + y = 2   →  y = 2 - x      and xy = 23  ...so....

x(2- x)= 23      expand

2x - x^2 = 23    rearrange

x^2 - 2x + 23 = 0    .....which implies that...

x^2 = 2x -23

And y^2 = (2 - x)^2 = (x -2)^2 = x^2 - 4x + 4

Therefore

x^2 + y^2 =

2x - 23 + x^2 - 4x + 4 =

x^2 - 2x - 19

CPhill  Jan 29, 2015
Sort:

#1
+17711
+5

Square both sides of the equation  x + y  = 2:

--->   (x + y)²  =  2²

Multiplying out:

--->  x² + 2xy + y²  =  4

Since xy = 23:

--->   x² + 23 + y²  =  4

--->   x² + y²  =  -19            (This does not have real answers!)

geno3141  Jan 29, 2015
#2
+18829
+5

If    and   ,  then what is    ?

$$(x+y)^2=x^2+2xy+y^2 \quad | \quad -2xy\\\\ x^2+y^2 =(\underbrace{x+y}_{=2})^2-2\underbrace{xy}_{=23}\\\\ x^2+y^2 = 2^2-2*23\\\\ x^2+y^2 = 4-46\\\\ x^2+y^2 = -42$$

heureka  Jan 29, 2015
#3
+81023
+5

Using x + y = 2   →  y = 2 - x      and xy = 23  ...so....

x(2- x)= 23      expand

2x - x^2 = 23    rearrange

x^2 - 2x + 23 = 0    .....which implies that...

x^2 = 2x -23

And y^2 = (2 - x)^2 = (x -2)^2 = x^2 - 4x + 4

Therefore

x^2 + y^2 =

2x - 23 + x^2 - 4x + 4 =

x^2 - 2x - 19

CPhill  Jan 29, 2015

### 6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details